Sequential crystallization and morphology of triple crystalline biodegradable PEO-b-PCL-b-PLLA triblock terpolymers. Issue 6 (11th January 2016) - Palacios, Jordana K.; Mugica, Agurtzane; Zubitur, Manuela; Iturrospe, Amaia; Arbe, Arantxa; Liu, Guoming; Wang, Dujin; Zhao, Junpeng; Hadjichristidis, Nikos; Müller, Alejandro J.
Abstract : The sequential crystallization of poly(ethylene oxide)- b -poly(ε-caprolactone)- b -poly(l -lactide) (PEO- b -PCL- b -PLLA) triblock terpolymers, in which the three blocks are able to crystallize separately and sequentially from the melt, is presented. Abstract : The sequential crystallization of poly(ethylene oxide)- b -poly(ε-caprolactone)- b -poly(l -lactide) (PEO- b -PCL- b -PLLA) triblock terpolymers, in which the three blocks are able to crystallize separately and sequentially from the melt, is presented. Two terpolymers with identical PEO and PCL block lengths and two different PLLA block lengths were prepared, thus the effect of increasing PLLA content on the crystallization behavior and morphology was evaluated. Wide angle X-ray scattering (WAXS) experiments performed on cooling from the melt confirmed the triple crystalline nature of these terpolymers and revealed that they crystallize in sequence: the PLLA block crystallizes first, then the PCL block, and finally the PEO block. Differential scanning calorimetry (DSC) analysis further demonstrated that the three blocks can crystallize from the melt when a low cooling rate is employed. The crystallization process takes place from a homogenous melt as indicated by small angle X-ray scattering (SAXS) experiments. The crystallization and melting enthalpies and temperatures of both PEO and PCL blocks decrease as PLLA content in the terpolymer increases. Polarized light optical microscopy (PLOM) demonstrated that the PLLA block templates the morphology of the terpolymer, as it forms spherulites upon cooling from the melt. The subsequent crystallization of PCL and PEO blocks occurs inside the interlamellar regions of the previously formed PLLA block spherulites. In this way, unique triple crystalline mixed spherulitic superstructures have been observed for the first time. As the PLLA content in the terpolymer is reduced the superstructural morphology changes from spherulites to a more axialitic-like structure.